Controvérsias sociocientíficas no ensino de ciências: usos da argumentação no caso do açaí transgênico na Amazônia - PEREIRA, Gerlany de Fátima dos Santos (Universidade Federal do Pará, 2021)
This study aimed to classify the arguments present in a Debate based on a Controversial Socio-Scientific (CSS) concerning to transgenic foods (TF) according to the Argumentation Theory of Chaїm Perelman and Lucie Olbrechts-Tyteca, and in different argumentative dimensions (scientific, environmental, social and economic). Taking as a methodological support the qualitative approach in the context of an action-research. The research was carried out at the Institute of Mathematical and Scientific Education of the Federal University of Pará, through the implementation of the Extension Course titled “Controversial Socio-scientific in Science Teaching”. Participated in the Course, 25 students of the Biological Sciences Degree from Federal University of Pará, 2009. The sampling was characterized by accessibility, since the students showed interest in the participation of the Course. The methodological strategy of action research was the Extension Course, based on the development of a fictitious case study, precisely “The simulated case of the transgenic açaí in the Amazon”, with the use of a set of activities that elicited discussions and arguments about CSS. For the analysis and interpretation of the data, the “Treatise on argumentation: the new rhetoric” was used as theoretical support in the light of Chaїm Perelman and Lucie Olbrechts-Tyteca. Two perspectives of analysis were the model proposed here. The first is related to the dimensions in which the arguments presented in the Debate were organized, namely: social, environmental, scientific, economic. The second is related to the classification of these arguments, according to Perelman and Olbrechts-Tyteca's theory of argument, into three main classes of argument: quasi-logical arguments, arguments based on the structure of the real and links that underlie the structure of the real. It can be said that the practice of argumentation was instituted, adding and articulating knowledge of diverse nature (scientific, environmental, economic, social, etc.). In general, the students avoided common sense, presenting negative and positive aspects about the TF, especially regarding its introduction in the Amazonian environment.